QUANTIFICATION DE L’EMISSION DE PLOMB DANS LE MILIEU URBAIN DE SIDI BEL’ ABBES (ALGERIE OCCIDENTALE) - Belhadj hanane; Hellal Benchaben; Ayad Nadira; Ayache Abbassia (European Scientific Journal, ESJ, 2015)
Quantification of lead emissions in the urban environment of Sidi Bel'Abbes (Western Algeria) is performed by the use of fronds Xanthoria parietina ( L.). Exposure of lichen thallus for a period of 30 days, was used to measure the concentrations of airborne lead in two seasons. Summer season was characterized by high concentrations of the order of 10.66 ± 2.08 ppm. Winter is the season against is characterized by low values of the order of 1.30 ± 0.10 ppm. The differences in the concentrations of airborne lead between and within seasons are due to the weather conditions, the unequal distribution of traffic and the presence of steep slopes in some neighborhoods. The rainy and windy seasons tend to reduce air pollution while the dense traffic and steep slopes only increase lead levels emitted by vehicles.